Gingival crevicular fluid: An overview - Krishnan Chandragiri Subbarao; Gowri Shankar Nattuthurai; Satheesh Khannaa Sundararajan; Indhu Sujith; Jennifer Joseph; Yasmin Parvin Syedshah (Wolters Kluwer Medknow Publications, 2019)
Gingival crevicular fluid is an inflammatory exudate derived from the periodontal tissues. It is composed of serum and locally generated materials such as tissue breakdown products, inflammatory mediators, and antibodies directed against dental plaque bacteria. It plays a special part in maintaining the structure of junctional epithelium and the antimicrobial defense of periodontium. Some of the suspected periodontal pathogens such as Porphyromonas gingivalis and Treponema denticola produce broad-spectrum neutral proteinases as part of their virulence arsenal. These proteinases may be detected in plaque and gingival crevicular fluid samples of patients with periodontitis. The potential diagnostic importance of gingival fluid was recognized more than six decades ago. The fluid component of gingival crevicular fluid is derived primarily from microvascular (postcapillary venule) leakage. There are number of distinct advantages and challenges of using gingival crevicular fluid as a diagnostic test for periodontal disease.